PERSENTASE KERUSAKAN DAN TOTAL BAKTERI SUSU SEGAR DI KELOMPOK PETERNAK SAPI PERAH ANDINI LESTARI DAN TIRTA SARI AJI KABUPATEN BANYUMAS - Abdurrahman, Isa Abdillah; subagyo, yusuf; Soediarto, Pramono (ANGON: Journal of Animal Science and Technology, 2020)
Background. The study was entitled "Percentage of Damage and Total Fresh Milk Bacteria in the Andini Lestari Dairy Farmer Group and Tirta Sari Aji Banyumas Regency". The purpose of this research was to determine percentage of damage and total bacteria in fress milk in the Andini Lestari dairy cattle group of Cilongok District and the Tirta Sari Aji dairy cattle in Karanglewas District. The research was conducted on 2 August 2019 until 28 September 2019. Materials and Methods. The material used is dairy farmers and milk. Dairy milk samples were obtained from 15 cattle from the Andini Lestari breeder group in Cilongok District and 15 cattle from Tirta Sari Aji, Karanglewas District, Banyumas Regency. The research method uses the survey method by conducting interviews and direct field observations. The response variables measured and observed in this study were milk damage and total milk bacteria. Milk samples obtained from the farms are then taken to the Dairy Production Laboratory for total microbial testing using the Total Plate Count Test and milk damage using the Alcohol Test. Results. The results showed that the alcohol test in the Andini Lestari group contained none positive samples or the presence of lumps in milk, while in the Tirta sari Aji group there were two positive samples of milk. Analysis of the sign test showed the level of milk damage in the two districts was not significantly different (P > 0.05). The results of total microbial studies in the two groups had an average of 16.22 x 104 cfu / ml and 14.44 x 104 cfu / ml. Analysis of the "t" test showed that the total microbes in the two groups were significantly different (P < 0.05). Conclusion. The quality of fresh milk in percentage of damage and total microbial in both Cilongok and Karanglewas Districts is considered good (according to SNI 2011).